The impact of Chikungunya chronic arthralgia on women's upper limbs motor function: a cross-sectional study - Germano Luís Rocha Machado; Rayane Quintão Castro; Ludimila Forechi; Heloísa da Costa Souza; Diogo Simões Fonseca; Marco Antonio Cavalcanti Garcia (Universidade de São Paulo, 2023)
ABSTRACT Post-Chikungunya chronic arthralgia (PCCA) may lead to musculoskeletal repercussions and functional loss. The objective was to assess the upper limb physical disability and symptoms during daily, work, and leisure activities of women presenting PCCA compared to healthy controls (HC). This was a cross-sectional study conducted with 52 women. The participants were divided into PCCA (37) and HC (15) groups. Handgrip strength, range of motion, level of pain (numerical rating scale), and participants' physical disability and symptoms (Disabilities of the Arm, Shoulder, and Hand Questionnaire - DASH) were evaluated. Differences between groups were evaluated using the Students t-test and Pearson's correlations. The chi-square test was applied for categorical variables. The significance was set at α=0.05. The disease duration was 19.5±13.1 months. We found no differences between groups for peak force (PCAA:23.6±7.4kgf; HC: 24.5±6.2kgf; p=0.676). The results showed a significant difference between groups regarding range of motion (PCCA: 63.5±17.3o; HC: 77.2±9.6o), level of hand pain (PCCA: 5.8±2.2; HC: 0.4±1.5), and upper limbs functional levels (PCCA: 44.5±17.4; HC: 16.2±20.5). Participants related severe difficulty or inability to perform tasks such as opening a jar (78.4%), placing objects above head height (48.7%), doing heavy household chores (56.8%), and gardening (51.4%). Impairment in the upper limb physical function in daily, work, and leisure activities shows the higher prevalence in the long-term.